2016
DOI: 10.4103/0301-4738.198843
|View full text |Cite
|
Sign up to set email alerts
|

The posterior iris-claw lens outcome study: 6-month follow-up

Abstract: Purpose:The purpose of this study was to evaluate functional and anatomical outcomes of posterior iris-claw intraocular lens (IOL) implant for correction of aphakia in eyes with inadequate capsular support.Materials and Methods:Prospective case series of 108 aphakic eyes with inadequate capsular support which underwent posterior iris-claw IOL with a 6-month follow-up period was conducted. The cases belonged to two clinical settings: elective secondary implantation and those with intraoperative posterior disloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 22 publications
2
20
0
8
Order By: Relevance
“…Concerning safety, CMT, ECD loss, and type and percentage of postoperative complications were comparable between the groups. At the end of follow-up, the CMT was not significantly different from the preoperative value in either group, which was consistent with previous studies [ 11 , 12 ]. We analyzed ECD loss at 1 and 12 months; loss at the first time point is assumed to mainly reflect intraoperative cellular loss, while ECD loss occurring between 1 month and 12 months is attributable to the presence of the IOL.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Concerning safety, CMT, ECD loss, and type and percentage of postoperative complications were comparable between the groups. At the end of follow-up, the CMT was not significantly different from the preoperative value in either group, which was consistent with previous studies [ 11 , 12 ]. We analyzed ECD loss at 1 and 12 months; loss at the first time point is assumed to mainly reflect intraoperative cellular loss, while ECD loss occurring between 1 month and 12 months is attributable to the presence of the IOL.…”
Section: Discussionsupporting
confidence: 92%
“…Iris-claw IOLs can also be securely fixed to the posterior surface of the iris, to maintain the physiological position of the diaphragm in the posterior chamber (PC) of the eye and thus reduce the potential for the complications associated with AC IOLs. Many investigators have reported relatively large series, both prospective and retrospective, demonstrating the midterm safety and efficacy of this procedure [ 9 12 ]. Both AC and PC iris-claw IOLs were also found to be safe and effective for visual rehabilitation in young patients [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hinsichtlich der Sicherheit waren ZND, EZD-Verlust sowie Art und Häufigkeit postoperativer Komplikationen in beiden Gruppen vergleichbar. Am Ende des Nachbeobachtungszeitraums unterschied sich die ZND in beiden Gruppen nicht signifikant vom präoperativen Wert, was sich mit den Ergebnissen früherer Studien deckt [11,12]. Wir analysierten den EZD-Verlust nach 1 und nach 12 Monaten; vom ersteren Wert wird angenommen, dass er hauptsächlich den intraoperativen Zellverlust widerspiegelt, während der EZD-Verlust zwischen dem ersten und dem zweiten Zeitpunkt auf das Vorhandensein der IOL zurückgeführt wird.…”
Section: Diskussionunclassified
“…Irisklauen-IOL können ebenso sicher an der posterioren Fläche der Iris fixiert werden, um die physiologische Position des Diaphragmas in der Hinterkammer (HK) aufrechtzuerhalten und so das Komplikationsrisiko zu verringern, das mit VK-IOL assoziiert ist. Viele Autoren haben über recht große Fallserien berichtet, sowohl prospektiv als auch retrospektiv, und haben damit die mittelfristige Sicherheit und Wirksamkeit des Eingriffs belegt [9,10,11,12]. Sowohl VK- als auch HK-Irisklauen-IOL haben sich als sicher und wirksam für die visuelle Rehabilitation bei jungen Menschen erwiesen [13,14].…”
Section: Introductionunclassified
“…Результаты иридоангиографии после имплантации современных моделей ирис-кло линз показывают незначительные изменения в радужной оболочке по сравнению с переднекамерной, зрачковой и шовной ирис-фиксацией. При этом ретропупиллярная имплантация ирис-кло ИОЛ способствует значительному уменьшению частоты развития и степени тяжести данного осложнения [28][29][30].…”
Section: обзоры литературыunclassified